Exploring suicide ideation in university students: sleep quality, social media, self-esteem, and barriers to seeking psychological help - Landa-Blanco, Miguel; Romero, Karol; Caballero, Ivin; Gálvez-Pineda, Ernesto; Fúnes-Henríquez, María José; Romero, Rina (Frontiers in Psychiatry, 2024)
The purpose of the current study is to analyze how variations in suicidal ideation scores can relate to sleep quality, social media consumption, self-esteem, and perceived barriers to seeking psychological help in a sample of university students in Honduras. A quantitative cross-sectional design was used. Self-reported data was collected from a non-random sample of 910 university students in Honduras; their average age was 24.03 years (SD=6.05). Most respondents were women (67%) with men accounting for 33% of the sample. Measurements included item 9 of the Patient Health Questionnaire-9, the Single-Item Sleep Quality Scale, Rosenberg’s Self-Esteem Scale, Barriers to Seeking Psychological Help Scale for College Students, and a self-reported questionnaire on social media. In response to the query, “Over the past two weeks, how frequently have you experienced thoughts that you would be better off dead or of hurting yourself?” 54% (n=495) of participants indicated “not at all” 18% (n=168) reported “several days” 14% (n=129) responded “more than half of the days” and 13% (n=118) stated “nearly every day”. The results from the ordinal logistic regression model indicate that sleep quality and self-esteem serve as protective factors associated with decreased suicide ideation. At the same time, a higher number of social media platforms used per week and perceived barriers to seeking psychological help increase suicide ideation. Altogether, these variables explained 19% of the variance in suicidal ideation scores. Suicidal ideation is highly prevalent among the sampled university students.